Technologically enhanced pedagogies in Professional Writing (Journal of Applied Learning and Teaching, 2019)
Development of online or hybrid options for academic content often emphasizes product over process. Institutions may decide to join the latest movement without carefully considering whether particular content lends itself to such technologies. The question to be asked first is whether students in a specific discipline — business, science, or another — would benefit from technological pedagogies instead of, or in tandem with, traditional offerings. Even though the “classroom” now can be virtually recreated with hyperlinked readings, synchronous chats, and real-time interactions, the instructor must vouchsafe an enriching learning environment. One endeavor across many — if not all — academic disciplines is written communication, through which students explore course content, critically assess meaning, and construct cogent arguments. Applied writing, often termed Professional Writing, weaves through the curricula at Widener University; open-access modules for at-risk students seeking a college education are also being developed with a local not-for-profit agency. Before shifting courses or modules to online and/or hybrid formats directly, Professional Writing faculty are designing, implementing, and assessing various tools: blended course design, online writing resources, and open-access outreach. The core pedagogical issue remains the astute application of technological tools to achieve learning outcomes. This presentation highlights progress by the Professional Writing faculty at Widener University for enhancing pedagogies with technology while navigating climate and culture.